2007
DOI: 10.1128/jcm.02366-06
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sequence Analysis of the NS5B Region for Routine Genotyping of Hepatitis C Virus with Reference to C/E1 and 5′ Untranslated Region Sequences

Abstract: Nucleotide sequence analysis of the NS5B region was performed to identify genotypes of 8,479 hepatitis C virus (HCV) RNA-positive patient samples collected in the Canadian province of Quebec. Genotypes could be determined for 97.3% of patients. Genotypes 1 to 6 were found in 59.4, 9.0, 25.7, 3.6, 0.6, and 1.8% of patients, respectively. Two isolates did not classify within the six genotypes. The subtype 1 distribution was 76.7% 1a, 22.6% 1b, and 0.7% others, while the subtype 2 distribution was 31.8% 2a, 47.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
259
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 266 publications
(287 citation statements)
references
References 48 publications
(51 reference statements)
13
259
1
11
Order By: Relevance
“…Remarkably, subtypes 6l and 6k were isolated from Vietnamese individuals (Lu et al, 2006(Lu et al, , 2007a. D85 on the other hand had 92.5 % sequence similarity to subtype 6o prototype strain QC227 isolated from an Asian immigrant in Canada (Murphy et al, 2007), confirmed by phylogeny of whole genome and short fragment analysis ( Fig. 1 and Supplementary Fig.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Remarkably, subtypes 6l and 6k were isolated from Vietnamese individuals (Lu et al, 2006(Lu et al, , 2007a. D85 on the other hand had 92.5 % sequence similarity to subtype 6o prototype strain QC227 isolated from an Asian immigrant in Canada (Murphy et al, 2007), confirmed by phylogeny of whole genome and short fragment analysis ( Fig. 1 and Supplementary Fig.…”
mentioning
confidence: 72%
“…Currently, genotype 6 viruses are classified into 17 subtypes (6a-6q) based on complete genome analysis (Lu et al, 2006(Lu et al, , 2007aTokita et al, 1996Tokita et al, , 1998. Recently, the existence of subtype 6r and 6s viruses was proposed based on sequence analysis of core/ E1 and NS5B from HCV strains isolated from Cambodian immigrants in Canada (Murphy et al, 2007). In addition, a subtype of some viruses could not be assigned and these were classified as novel candidate HCV genotype 6 (Lu et al, 2006;Shinji et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The branch leading to the three isolates appeared equivalent to the branches directing the 6a-6q and km41 and gz52557 genomes. Consequently, VT21, TV241 and TV249 were assigned to subtype 6t, following the recently described 6r and 6s subtypes (Murphy et al, 2007). Within genotype 6, four major groups were formed.…”
Section: Phylogenetic Analysis Of the Complete Sequencesmentioning
confidence: 99%
“…Among them, D49 (GenBank accession nos DQ155472 and DQ155530) was from a blood donor in Vietnam with partial sequences available in the core and NS5B regions (Noppornpanth et al, 2006). QC131 (GenBank accession nos EF115932 and EF116155), QC145 (EF115934 and EF116157), QC240 (EF115948 and EF116171) and QC351 (EU127994 and EU127995) were from Vietnamese immigrants in Quebec, Canada with partial sequences available in the E1 and NS5B regions (Murphy et al, 2007). The finding of five additional isolates grouping with VT21, TV241 and TV249 in patients originating from Vietnam consolidates the designation of this new subtype.…”
Section: Phylogenetic Analysis With Database Sequencesmentioning
confidence: 99%